Reduction of mitochondria and up regulation of pyruvate dehydrogenase kinase 4 of skeletal muscle in patients with chronic kidney disease. Issue 3 (7th June 2019) - Xu, Chenqi; Kasimumali, Ayijiaken; Guo, Xiangjiang; Lu, Renhua; Xie, Kewei; Zhu, Mingli; Qian, Yingying; Chen, Xiaohuan; Pang, Huihua; Wang, Qin; Fan, Zhuping; Dai, Huili; et al.
ABSTRACT: Aim: Muscle weakness is commonly among chronic kidney disease (CKD) patients. Muscle mitochondrial dysfunction and decreased pyruvate dehydrogenase (PDH) activity occur in CKD animals but have not been confirmed in humans, and changes in pyruvate dehydrogenase kinase (PDK) and pyruvate dehydrogenase phosphatase (PDP) expression have not been evaluated in CKD muscle. We presume that the reduction of muscle mitochondria and post‐translational modification of PDH may cause muscle weakness in CKD patients. Herein, we explored changes in mitochondrial morphology, PDH expression and activity, and PDK/PDP expression in CKD patient muscle. Methods: Twenty patients with stage 4–5 CKD (CKD group) and 24 volunteers (control group) were included. Clinical characteristics, biochemical information and handgrip strength (HGS) were determined. Skeletal muscle samples were collected from eight stage 5 CKD patients from CKD group. Other eight non‐CKD surgical subjects' muscle samples were collected as control. PDH activity was determined using a PDH enzyme activity assay kit, and real‐time PCR and western blotting analyses were performed to measure gene expression and protein levels, respectively. Transmission electron microscopy was used to study mitochondria morphology. Results: CKD patients had lower HGS than non‐CKD subjects, and HGS was correlated with gender, age, haemoglobin and albumin. Mitochondria were decreased in end‐stage renal disease (ESRD) patients muscle. Mfn‐1 expression and phospho‐Drp1(S637)/Drp1 ratio were inhibited in the ESRD group, implicating dysfunctional mitochondrial dynamics. Muscle PDH activity and phospho‐PDH(S293) were decreased in ESRD patient muscle, while PDK4 protein level was up regulated. Conclusion: Decreased mitochondria and PDH deficiency caused by up regulation of PDK 4 contribute to muscle dysfunction, and could be responsible for muscle weakness in CKD patients. SUMMARY AT A GLANCE: The present study investigated changes in mitochondrial morphology and pyruvate dehydrogenase (PDH) activity and pyruvate dehydrogenase kinase 4 (PDK4) expression in muscle of human chronic kidney disease (CKD). Decreased mitochondria in association with reduced Mfn‐1 and phospho‐Drp1(S637)/Drp1 ratio suggested dysfunctional mitochondrial dynamics, which, together with reduced PDH activity and PDK4 upregulation, may account for muscle weakness in CKD.